(Cambridge O Level) English language coursebook (second edition) - Toner, Helen; Reynolds, John (Cambridge University Press Cambridge, 2016)
Cambridge O Level English Second Edition has been written for students preparing for Cambridge O Level in English Language, conducted by Cambridge International Examinations.